A psychological profile of drivers convicted of driving under the influence of alcohol - Escamilla, Cristina; Beleña, M. Ángeles; Picó, Alfonso; Mora Rojo, Jorge; Mateu-Mollá, Joaquín (Transportation Research Part F: Traffic Psychology and Behaviour, 2023)
Driving under the influence of alcohol (driving while intoxicated [DWI]) is a rather large social problem. It can be influenced by the driver's personality, risk perception, difficulties related to hyperactivity, or attention deficit and alcohol dependencies; all of which share complex relations with each other, increasing the probability of criminal behaviour while driving and of road accidents. The purpose of this study is to explore the way in which personality, personality disorders, risk perception and behaviour while driving, hyperactivity or attention deficit, and the problematic consumption of alcohol are expressed in a sample of Spanish drivers who had been found guilty of committing DWI offences. These results are compared with those recorded for a sample of drivers with no history of such violations. For this study, a total of 115 subjects sentenced to perform road safety-related community service work (CSW) as a result of DWI convictions, as well as 97 drivers with no violations, were evaluated using Driver Behaviour Questionnaire (DBQ) tests, the NEO Five-Factor Inventory (NEO-FFI), the International Personality Disorder Examination (IPDE), the Adult ADHD Self-Report Scale Version 1.1, and the Alcohol Use Disorders Identification Test (AUDIT). Our results reveal that DWI traffic offenders exhibit risky consumption and signs of dependence (on alcohol and/or other drugs), and low levels of risk perception that are significantly lower than those observed for drivers without infractions. The logistic regression model provides data that supports the implication of a low perception of risk while driving under the influence of alcohol or other drugs, the violation of rules, extroverted personality traits, openness and cordiality, the indications of possible paranoid and antisocial PDs, and a below-university level of education as predictors of road crime due to DWI. This statistical solution offers a classificatory model with adequate internal and external validity. This scientific evidence could be useful for the design and improvement of prevention and reinsertion plans.
Keywords: attention deficit hyperactivity disorder; driving under the influence of alcohol; personality; risk behaviour; risk perception; road crime; Scopus; JCR